Pengaruh Marketing Mix Pada Pengguna Jasa Penginapan Di Hotel Kota Banda Aceh - amelia, kiki putri; havizatun, melvi (Fakultas Ekonomi, 2023)
This study aims to examine how much influence the marketing mix consisting of (Product, Price, Place, Promotion, People, Physical Evidence, and Process) has on consumers' decisions to use services at the Mecca Hotel Banda Aceh, either simultans or partially. Data collection techniques were collected through a list of questions/questionnaires and documentation studies. The sample size of this study was 100 respondents who had visited the Mecca Hotel Banda Aceh and were willing to become respondents. Hypothesis testing using multiple linear regression analysis, F test (simultans) and T test (partial) is intended to determine simultaneously and partially the effect of the independent variable on the dependent variable at the 95% confidence level (α = 0.05). The results showed that partially the product had an effect on consumer decisions to use the services at the Mecca Hotel Banda Aceh. Price has no effect on consumer decisions to use services at the Mecca Hotel Banda Aceh. Place affects consumer decisions to use services at the Mecca Hotel Banda Aceh. Promotion has no effect on consumer decisions to use the services of the Mecca Hotel Banda Aceh. People influence consumer decisions to use the services of the Mecca Hotel Banda Aceh. Physical evidence influences consumer decisions to use services at the Mecca Hotel Banda Aceh. The process influences the consumer's decision to use the services at the Hotel Mecca Banda Aceh. And simultaneously that Product, Price, Location, Promotion, People, Physical Evidence, and Process affect consumer decisions to use services at the Mecca Hotel.